THE LANGUAGE REGIME OF THE EUROPEAN UNION - Alves, Luísa Verdelho (2014)
The linguistic pluralism that characterizes the legal system of the European Union is one of the most unique features of European integration process. And it is also one of its greatest challenges. The language configuration of the European Union illustrates the paradoxes of the integration process, which are eloquently expressed in the motto adopted by the Union – "united in diversity". The language issue has given rise to an intense doctrinal debate that confronts the desideratum of linguistic diversity with other dimensions of a project that aspires to a "closer union among the peoples." Too often, however,this discussion is based on misunderstandings of the language regime of the European Union. This article presents an overview of the rules concerning the use of language in the European Union. This analysis will show that the language regime of the European Union does not guarantee equality of the Member States languages. Instead, the language regime of the European Union establishes a sort of multilingualism of varying intensities. Nevertheless, it recognizes citizens' right to speak their language, if that language is one of the twenty four official languages of the Union, in communication with the institutions and advisory bodies of the Union, in addition to ensuring access to Union legislation and justice in one of the languages of the Union.